2011
DOI: 10.1002/qj.855
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of the London urban heat island

Abstract: We present simulations of London's meteorology using the Met Office Unified Model with a new, sophisticated surface energy-balance scheme to represent the urban surfaces, called MORUSES. Simulations are performed with the urban surfaces represented and with the urban surfaces replaced with grass in order to calculate the urban increment on the local meteorology. The local urban effects were moderated to some extent by the passage of an onshore flow that propagated up the Thames estuary and across the city, coo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
185
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(209 citation statements)
references
References 37 publications
12
185
1
Order By: Relevance
“…Klysik and Fortuniak 1999;Bohnenstengel et al 2011;Azevedo et al 2016), they do not explicitly separate urban heat advection from the UHI signal (i.e. (i) the locally generated UHI component with intensity dependent upon underlying land use, and (ii) the urban heat advection that is generated from upwind urban land use).…”
Section: Urban Heat Advectionmentioning
confidence: 99%
“…Klysik and Fortuniak 1999;Bohnenstengel et al 2011;Azevedo et al 2016), they do not explicitly separate urban heat advection from the UHI signal (i.e. (i) the locally generated UHI component with intensity dependent upon underlying land use, and (ii) the urban heat advection that is generated from upwind urban land use).…”
Section: Urban Heat Advectionmentioning
confidence: 99%
“…The UHI exacerbates heat waves during the summer, increases energy consumption, and more importantly elevates the risk of heat-related morbidity and mortality, especially for the elderly, young children, and low-income residents, who are more vulnerable to excessive heat stress due to a variety of physical, social, and economic reasons [5][6][7][8][9]. Many existing studies have made attempts to understand and mitigate UHI effect in major cities all over the world, such as London, Beijing, Paris, Shanghai, Hong Kong, and Moscow [10][11][12][13][14][15][16]. UHI mitigation via sustainable design of the urban environment has received increasing attention from ecologists, urban planners, and policymakers.…”
Section: Introductionmentioning
confidence: 99%
“…Further, sources of anthropogenic heat emission, for example, vehicles, buildings and industry, add to the heat emission and affect the overall heat balance (Taha 1997;Ichinose, Shimodozono, and Hanaki 1999;Offerle, Grimmond, and Fortuniak 2005;Hamilton et al 2009;Sailor 2010) and have been shown to increase the temperature due to the UHI, i.e. the UHI increment (UHII) by 1-2 • C (Ichinose, Shimodozono, and Hanaki 1999;Bohnenstengel et al 2011). This source of additional energy release is added as a positive value to the surface energy balance.…”
Section: The Uhimentioning
confidence: 99%
“…London's UHI is well described (for example, Howard 1818; Watkins et al 2002;Kolokotroni and Giridharan 2008;Bohnenstengel et al 2011;Mavrogianni et al 2011), and the nocturnal summertime UHII has been shown to be approximately 2 • C (Kolokotroni and Giridharan 2008). During periods of extreme weather, for example, the 2003 heat wave, parts of central London were up to 10 • C warmer than the surrounding rural zone (GLA 2010).…”
Section: London's Uhimentioning
confidence: 99%